2006
DOI: 10.1302/0301-620x.88b1.16807
|View full text |Cite
|
Sign up to set email alerts
|

An equinus deformity of the ankle accounts for only a small amount of the increased forefoot plantar pressure in patients with diabetes

Abstract: Patients with diabetes mellitus may develop plantar flexion contractures (equinus) which may increase forefoot pressure during walking. In order to determine the relationship between equinus and forefoot pressure, we measured forefoot pressure during walking in 27 adult diabetics with a mean age of 66.3 years (sd 7.4) and a mean duration of the condition of 13.4 years (sd 12.6) using an Emed mat. Maximum dorsiflexion of the ankle was determined using a custom device which an examiner used to apply a dorsiflexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…Previous methodologies have involved the use of various devices in evaluating ankle stiffness and ROM. [1][2][3] Assessment of these parameters is particularly important for orthotists to enable them to determine the mechanical properties required in an ankle-foot orthosis (AFO) design. The mechanical characteristics of AFOs and the physiological characteristics of an anatomical ankle joint need to be matched to maximize the benefit from an orthotic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Previous methodologies have involved the use of various devices in evaluating ankle stiffness and ROM. [1][2][3] Assessment of these parameters is particularly important for orthotists to enable them to determine the mechanical properties required in an ankle-foot orthosis (AFO) design. The mechanical characteristics of AFOs and the physiological characteristics of an anatomical ankle joint need to be matched to maximize the benefit from an orthotic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical biomechanical studies have shown that the range of movement of the ankle accounts for only a small proportion of forefoot plantar pressure in both diabetic patients and asymptomatic subjects. 51,52 Lengthening of the tendo-Achillis has been shown initially to reduce plantar pressure by 27%, but it returned to very high values after eight months and persisted thereafter. 53 Based on these reports we only used tendo-Achillis lengthening in selected patients at the end of our staged protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Orendurff and colleagues 423 found from studies on a group of 27 diabetic patients that only 14% of the variance in forefoot plantar pressure could be accounted for by equinus deformity. Therefore, they recommended caution in using TAL procedures to relieve forefoot pressure.…”
Section: Surgery To Alter Biomechanicsmentioning
confidence: 99%